Graphitic Carbon Nitride/Nickel Oxide/Pt Heterojunction Photocatalysts for Hydrogen Production from Ammonia Borane Under White-Light Irradiation - Korkut, Sibel Eken; Aksoy, Merve; Metin, Oender (WILEY-V C H VERLAG GMBH, 2025)
Graphitic carbon nitride/Nickel oxide-X (gCN/NiO-X, where X represents the Ni wt%) binary heterojunctions were synthesized using a simple method and then platinum nanoparticles (Pt NPs) were then in situ generated on the gCN/NiO-X binary heterojunctions by reducing the pre-anchored Pt ions during the hydrolysis of ammonia borane (HAB) under white-light irradiation. The gCN/NiO-3.12%/Pt(IV) heterojunctions, with 1.31 wt% Pt, exhibited the highest turnover frequency (TOF) of 132.9 mol H-2 mol Pt-(1) min-(1) in hydrogen generation from AB hydrolysis, which is 1.9 times higher than that of gCN/Pt(IV) nanocomposites. The enhanced activity of the gCN/NiO/Pt nanocatalysts can be attributed to the heterojunction formed between gCN and NiO, which facilitates greater visible-light absorption, more efficient photo-induced charge separation, and improved charge carrier transfer compared to the gCN/Pt nanocatalysts in photo-assisted HAB. Reusability tests demonstrated that the gCN/NiO/Pt heterojunction photocatalysts retained 84% of their initial hydrogen generation rate (mL H-2/min) after five consecutive runs of HAB. For the first time, this study demonstrates that the gCN/NiO binary heterojunctions are easily synthesized and to be preferred as the photoactive support materials for the in situ growth of Pt NPs as catalysts for not only hydrogen generation but also other chemical transformations.
Keywords: Graphitic carbon nitride; Heterojunction; Hydrogen production; Nickel oxide; Photocatalyst; NICKEL-OXIDE; NANOPARTICLES; HYDROLYSIS; CATALYSTS; DEHYDROGENATION; NANOCOMPOSITES; PHOTOREDUCTION; CHALLENGES; NANOSHEETS; MECHANISM; Chemistry